A kinematic excess in the annular gap and gas-depleted cavity in the disc around HD 169142. Issue 4 (25th November 2022) - Garg, H; Pinte, C; Hammond, I; Teague, R; Hilder, T; Price, D J; Calcino, J; Christiaens, V; Poblete, P P
ABSTRACT: We present ALMA band 6 images of the 12 CO, 13 CO, and C 18 O J  = 2-1 line emissions for the circumstellar disc around HD 169142, at ∼8 au spatial resolution. We resolve a central gas-depleted cavity, along with two independent near-symmetric ring-like structures in line emission: a well-defined inner gas ring [∼25 au] and a second relatively fainter and diffuse outer gas ring [∼65 au]. We identify a localized super-Keplerian feature or vertical flow with a magnitude of ∼75 ms −1 in the 12 CO map. This feature has the shape of an arc that spans azimuthally across a position angle range of −60° to 45° and radially in between the B1[26au] and B2[59au] dust rings. Through reconstruction of the gas surface density profile, we find that the magnitude of the background perturbations by the pressure support and self-gravity terms are not significant enough to account for the kinematic excess. If of planetary origin, the relative depletion in the gas-density profile would suggest a 1 MJ planet. In contrast, the central cavity displays relatively smooth kinematics, suggesting either a low-mass companion and/or a binary orbit with a minimal vertical velocity component.